APRIMORAMENTO DA CONSCIÊNCIA SINTÁTICA E SEUS REFLEXOS NA QUALIDADE ARGUMENTATIVA EM TEXTOS DE ESTUDANTES DO ENSINO MÉDIO - Ana Paula Teixeira de Amorin (2024)
This thesis is developed in line with the idea of promoting a more reflective approach to linguistic analysis in Portuguese language classes. Its main focus is on the influence of syntactic awareness development (Vieira; Faraco, 2020) on the argumentative skills of students newly enrolled in high school, within the framework of a functionally oriented teaching approach (Neves, 2018). The underlying hypothesis is that, when constructing their texts, students display certain syntactic-semantic inaccuracies and/or a weakening of the connections between ideas, as they activate insufficient syntactic resources in the construction of textual components. Particular emphasis is placed on complex sentences, which are more conducive to argumentative writing due to their potential to articulate more sophisticated ideas and reasoning. Such aspects are often mediated through traditional grammar, preventing students from fully understanding their authentic roles in textual production. Therefore, it is posited that these aspects can be improved when presented in a more functional manner. The primary objective is to analyze the relationship between the enhancement of syntactic awareness and the ability to argue coherently in written texts, identifying how this relationship contributes to an increase in the level of informativeness and argumentative progression within students’ texts. The specific objectives include: a) comparing, at different stages of the students' academic journey, the features indicating the development of syntactic awareness observed in their argumentative texts; b) qualitatively and quantitatively describing the various syntactic mechanisms that reflect syntactic-semantic operations activated by students, considering the textual genre and the Didactic Sequence they participated in; and c) demonstrating how these mechanisms can enhance the persuasive nature expected from the textual genre, through the observation of levels of informativeness and argumentativity in students' productions. For a more longitudinal follow-up of the students, a Didactic Sequence (Dolz; Noverraz; Schneuwly, 2004) was implemented, organized around the genre of the “argumentative essay” as adopted in Brazil's National High School Exam (ENEM), and exercises that focused on syntactic aspects of written language. The resulting texts revealed two main findings: (i) the progression of syntactic awareness, which is not static but presents continuous development that influences textual organization and overall structure; and (ii) the argumentative and discursive potential of the texts, as strong syntactic organization not only improves clarity and cohesion but also elevates the text to a higher level of persuasion, making it more effective in convincing the reader. The results emphasize the importance of sentence structuring and textual coherence, as well as the syntactic and semantic relationships established, all of which contribute directly to persuasion by strengthening the text’s informativeness and argumentative progression. Keywords: Syntactic Awareness. Argumentative Essay. Didactic Sequence. Basic Education. ENEM.